MADRASAH FOR ALL A CRITICAL DISCOURSE AND POLICY ANALYSIS OF EDUCATIONAL ACCESS FOR NON-MUSLIM STUDENTS IN INDONESIA - Ali Marzuki Zebua; Khairul Anwar; Reno Diqqi Alghzali (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study examines the phenomenon of non-Muslim students enrolling in Indonesian madrasahs and analyzes the educational policies governing their admission, with particular attention to the implementation of their right to receive religious education according to their faith. This study employs qualitative library research using Fairclough's Critical Discourse Analysis (CDA) combined with Public Policy Analysis, which involves a review of Government Regulation No. 55/2007 and various related media sources. The results show that although the legal framework guarantees non-Muslim students the right to religious education, its implementation remains inconsistent. Consequently, many students continue to experience uncertainty and unequal treatment in the fulfillment of these rights. The findings indicate that these challenges can be overcome through more inclusive and adaptive policies, as well as raising awareness among stakeholders about the importance of diverse education in madrasahs. Recommendations include revising regulations to clarify admission procedures, developing inclusive curricula and training teachers in managing diverse classrooms, so that madrasahs can serve as agents of social change that support interfaith integration and tolerance in Indonesia.